Provision of health care actions and services for the management of HIV/AIDS from the users’ perspective - Figueiredo, Luana Alves; Lopes, Lívia Maria; Magnabosco, Gabriela Tavares; Andrade, Rubia Laine de Paula; Faria, Mayara Falico; Goulart, Vanessa Camarinha; Scatena, Lucia Marina; Nogueira, Jordana de Almeida; Pinto, Ione Carvalho; Arcencio, Ricardo Alexandre; Palha, Pedro Fredemir; Villa, Tereza Cristina Scatena; et al. (Revista da Escola de Enfermagem da USP, 2014)
Objective To analyse the provision of health care actions and services for people living with AIDS and receiving specialised care in Ribeirão Preto, SP. Method A descriptive, exploratory, survey-type study that consisted of interviews with structured questionnaires and data analysis using descriptive statistics. Results The provision of health care actions and services is perceived as fair. For the 301 subjects, routine care provided by the reference team, laboratory tests and the availability of antiretroviral drugs, vaccines and condoms obtained satisfactory evaluations. The provision of tests for the prevention and diagnosis of comorbidities was assessed as fair, whereas the provisions of specialised care by other professionals, psychosocial support groups and medicines for the prevention of antiretroviral side effects were assessed as unsatisfactory. Conclusion Shortcomings were observed in follow-up and care management along with a predominantly biological, doctor-centred focus in which clinical control and access to antiretroviral therapy comprise the essential focus of the care provided.